2021
DOI: 10.1088/1674-4527/21/7/174
|View full text |Cite
|
Sign up to set email alerts
|

A photometric study of two neglected eclipsing binaries

Abstract: We present the first BVR photometry, period variation and photometric light curve analysis of two poorly studied eclipsing binaries, V1321 Cyg and CR Tau. Observations were carried out from November 2017 to January 2020 at the observatory of Uzhhorod National University. Period variations were studied using all available early published as well as our minima times. We used the newly developed ELISa code for the light curve analysis and determination of photometric parameters for both systems. We found that V13… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The first photometric solution of the GSC 04364-00648 light curves revealed that the system is semi-detached binary, where a cool secondary component almost fills its Roche lobe, as detected in some other near-contact systems, like EG Cep (Djurašević et al 2013) or CR Tau (Kudak et al 2021). Although we can see some quadratic changes on the O − C diagram, which corresponds to a period decrease with a high rate of −2.26(5) × 10 −5 d/yr −1 , we cannot make strict conclusions about period variations in the system, mainly due to the short time (2019)(2020)(2021)…”
Section: Discussionmentioning
confidence: 81%
“…The first photometric solution of the GSC 04364-00648 light curves revealed that the system is semi-detached binary, where a cool secondary component almost fills its Roche lobe, as detected in some other near-contact systems, like EG Cep (Djurašević et al 2013) or CR Tau (Kudak et al 2021). Although we can see some quadratic changes on the O − C diagram, which corresponds to a period decrease with a high rate of −2.26(5) × 10 −5 d/yr −1 , we cannot make strict conclusions about period variations in the system, mainly due to the short time (2019)(2020)(2021)…”
Section: Discussionmentioning
confidence: 81%
“…The first photometric solution of GSC 04364-00648 light curves revealed that the system is semi-detached binary, where a cool secondary component almost fills its Roche lobe as detected in some other near-contact systems, like EG Cep (Djurašević et al 2013) or CR Tau (Kudak et al 2021). Although we can see some quadratic changes on the O − C diagram, which corresponds to a period decrease with a high rate of −2.26(5) × 10 −5 d/yr −1 , we cannot make strict conclusions about period variation in the system, mainly due to short time (2019-2021) and uneven coverage of O − C diagram.…”
Section: Discussionmentioning
confidence: 86%